The christian democracy and the catholic church during the last dictatorship. Catholicism, politics and human rights - Fabris, Mariano (Universidad Nacional del Litoral, 2018)
This article seeks to shed light on the links between the Christian Democratic Party and the Catholic Church in recent history. With this purpose, are analyzed the positions assumed by a group of Christian-democratic leaders in the post coup d’État of 1976 and during the political opening phase that took place, with limits, in 1981.